The association between psychological strain and suicidal behaviors among college students: a mental health survey in Jilin Province, Northeast China - Song, Yan; Bai, Wei; Wang, Mohan; Liu, Xinyu; Zhang, Lili; Yu, Weiying; Li, Yuanyuan; Hua, Wanqing; Lew, Bob; Abu Talib, Mansor; Kou, Changgui (Elsevier, 2019)
Background : Suicide is a major global mental health problem among college students. The aim of the current study was to explore the association between the psychological strains of the strain theory of suicide and suicidal behaviors among college students.Methods : Participants comprised 1912 college students (16–28 years old, 47.2% female) from three universities in Jilin Province, China, who completed the self-report assessments of psychological strains (40 items Psychological Strains Scale) and suicidal behaviors (Suicidal Behaviors Questionnaire-Revised). The demographic characteristics included four variables: health status, psychological status, academic status and economic status.Results: Approximately 15.0% (286/1912) of participants were classified as having suicide risk, based on the cut-off scores of the SBQ-R. The prevalence of suicidal behaviors among males and females was 11.9% (120/1009) and 18.4% (166/903), respectively. Value strain (OR = 1.075, 95%CI: 1.057–1.094), aspiration strain (OR = 1.082, 95%CI: 1.064–1.101), deprivation strain (OR = 1.073, 95%CI: 1.052–1.093), and coping strain (OR = 1.095, 95%CI: 1.075–1.116) were risk factors for suicidality in college students. Coping strain (OR = 1.050, 95%CI: 1.023–1.077) was still positively associated with suicide risk in multivariate logistic regression. Logistic regression analysis indicated that coping strain had the highest correlation with suicidal behaviors.Limitations: The directionality of the relationships cannot be deduced because this study is cross-sectional.Conclusion: This study confirms a strong association between psychological strains and suicidal behaviors in college students. Some measures can be taken to reduce psychological strains to mitigate suicide risk among college students. More studies investigating coping strain among college students are warranted.